The English Catholic community, 1688-1745 : politics, culture and ideology - Glickman, Gabriel (Studies in early modern cultural, political and social history ;, 2009)
"The half-century following the Glorious Revolution has been viewed as a time of retreat and withdrawal for English Catholics: the response to tightening penal laws, periods in exile and the failures of the Jacobite cause. This book argues that the perception has arisen because research has been directed into the wrong places. It aims to recapture the eighteenth-century Catholic 'recusant' imagination through a study of hitherto unexplored treatises, manuscript literature and private correspondence preserved in family and religious archives. Contrary to the image of seclusion, Catholic lives were penetrated by questions of national identity, religious liberty and the authority of an international church: conflicts experienced not merely within their own nation, but in the European courts, seminaries and universities that supported them in exile. Their writings can be understood as commentaries on the state of a community trapped between the political, cultural and intellectual divisions that cut across the Roman Catholic world. Many were actively promoting change in church and state within Britain and Europe, and their arguments shaped the emergence of a 'Catholic Enlightenment' that outlasted the commitment to Jacobitism. The English Catholic Community investigates Catholic education and family life, scholarship, poetry and spirituality. It offers a fresh contribution to debates surrounding the history of the Jacobite movement, the construction of British national identity, and the origins of the Enlightenment. Gabriel Glickman is a lecturer in history at the University of Oxford."--